TRENDS OF RURAL-URBAN MIGRATION IN NIGERIA - Abbass, Isah Mohammed (European Scientific Journal, ESJ, 2012)
Given the tremendous explosions of urban settlements and the decadence of rural areas during the past two or three decades, the myth, reality and hope of a sustainable human settlement pattern seem to have been unraveled by the two UN Habitat Conferences of 1976 and 1996. Even though the wide range, tempting and unresolved human settlement issues have for long been grappled with by the public policies, solutions to the problems have continued to remain a mystery in Nigeria.Migration is not a recent human phenomenon. Over time however, human beings have moved and established settlements in dual albeit with stratified socio-economic and geo-political compositions called either ‘rural’ or ‘urban’. This paper attempts to examine and analyze the general problems of development of urban and rural settlements in Nigeria as well as various shifts in policies and strategies contained therein. However, it shows how and why efforts are concentrated more explicitly on urban settlements. These top-down manifestations of the growth centre strategies with a ‘trickle-down’ pattern, either in a spontaneous or induced manner, have evoked a reminiscence of other development paradigms and the futility of the approaches adopted, which are urban and industrial in nature, externally oriented and characterized by a highly advanced and capital intensive technology. Thus, artificially created Nigerian urbanized settlements are therefore not free from the intricacies of international dependency position, masterminded by MNCs, sanctioned by the Nigerian State and collaborated by the political and economic elites.